2018
DOI: 10.1038/sdata.2018.56
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of arable and abandoned land across former Soviet Union countries

Abstract: Knowledge of the spatial distribution of agricultural abandonment following the collapse of the Soviet Union is highly uncertain. To help improve this situation, we have developed a new map of arable and abandoned land for 2010 at a 10 arc-second resolution. We have fused together existing land cover and land use maps at different temporal and spatial scales for the former Soviet Union (fSU) using a training data set collected from visual interpretation of very high resolution (VHR) imagery. We have also colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 50 publications
2
74
0
Order By: Relevance
“…However, at the beginning of Kazakhstan's transition to a market economy, many lands were abandoned or at least they were not ploughed and were used mainly as pastures [65,66]. The reason for not ploughing the land is the socioeconomic situation prevailing not only in Kazakhstan but also in many post-communist countries from 1990 to about the beginning of 2000 [67][68][69][70]. The development of this phenomenon was facilitated by the loss of a guaranteed grain sales markets and by the deterioration of price relations between the value of manufactured products and their sale during the transition period.…”
Section: Peri-urban Areamentioning
confidence: 99%
“…However, at the beginning of Kazakhstan's transition to a market economy, many lands were abandoned or at least they were not ploughed and were used mainly as pastures [65,66]. The reason for not ploughing the land is the socioeconomic situation prevailing not only in Kazakhstan but also in many post-communist countries from 1990 to about the beginning of 2000 [67][68][69][70]. The development of this phenomenon was facilitated by the loss of a guaranteed grain sales markets and by the deterioration of price relations between the value of manufactured products and their sale during the transition period.…”
Section: Peri-urban Areamentioning
confidence: 99%
“…; Lesiv et al. ). In addition, livestock numbers collapsed after 1991, with declines of up to 80% in Kazakhstan (Kamp et al.…”
Section: Introductionmentioning
confidence: 98%
“…The contour map shown in Fig. 1 is based on data from Lesiv et al, 2018, and reflects the spatial patterns of changes in the structure of arable land in parts of the Central Non-Chernozem region. Compiled according to data provided by (Lesiv et al, 2018) The largest overgrowth of tree and shrub vegetation during the 2000s is observed in the northern part of the region within the landscape zone of mixed coniferous and broad-leaved forests in Smolensk, Tver, Kostroma, Yaroslavl, and Ivanovo regions (Fig.…”
mentioning
confidence: 99%